2014
DOI: 10.12998/wjcc.v2.i3.52
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective chart review of skin cancer presence in the wide excisions

Abstract: Our study indicates that approximately 50% or more of BCC and SCC patients with positive margins found on biopsies did not have cancer cells present at the time of wide excisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…This is not surprising, given that the previous study was conducted using tumor debulk specimens, which are almost always positive for tumor. In this study, approximately 70% of all specimens had no residual cancer reported on conventional histology, consistent with previously reported non-residual tumor rates of 27-85% in KC excisions (41)(42)(43).…”
Section: Comparisons Of Sensitivities and Specificitiessupporting
confidence: 92%
See 1 more Smart Citation
“…This is not surprising, given that the previous study was conducted using tumor debulk specimens, which are almost always positive for tumor. In this study, approximately 70% of all specimens had no residual cancer reported on conventional histology, consistent with previously reported non-residual tumor rates of 27-85% in KC excisions (41)(42)(43).…”
Section: Comparisons Of Sensitivities and Specificitiessupporting
confidence: 92%
“…Current recommended surgical margins, largely established many decades ago, are 4-to-6-mm for BCC and SCC for standard excision, depending on the histopathological subtypes (52,53). The findings that the majority of specimens reveal no residual cancer on histopathological assessment (70% in this study and 27-85% in literature) (41)(42)(43)54) suggest the possibility that current recommendations for surgical margins may be greater than clinically necessary. Reducing margin sizes may be feasible with the ability to ascertain the tumor margins during surgery.…”
Section: Clinical Advantages Envisionedmentioning
confidence: 65%
“…Previous studies report advanced HNBCC in the setting of neglected lesions that have been allowed to progress beyond typical presentation. 16-19 However, in this study, 19 lesions (50%) were recurrent upon presentation, confirming a unique subset of HNBCC patients who had aggressive and recalcitrant disease despite receiving medical care. This finding also underscores the importance of vigilant follow-up.…”
Section: Discussionsupporting
confidence: 51%
“…One alternative hypothesizes that inflammation associated with the acute healing process following shave biopsy leads to clearance of the residual tumor cells. 7 , 8 , 11 Another possibility is that once most of the tumor burden is mechanically removed, the patient’s immune system is able to clear the minimal residual tumor cell load. Alternatively, the pathological preparation of excisional specimens could cause a false-negative result simply by the nature of which pathologic examination is conducted (ie, not all possible sections of the specimen are examined under the microscope).…”
Section: Discussionmentioning
confidence: 99%